Events of increased biodiversity - Neige, Pascal, 1966- (Oxford : Elsevier Ltd., 2015)
The fossil record offers a surprising image: that of evolutionary radiations characterized by intense increases in cash or by the sudden diversification of a single species group, while others stagnate or die out. In a modern world, science carries an often pessimistic message, surrounded by studies of global warming and its effects, extinction crisis, emerging diseases and invasive species. This book fuels frequent'optimism' of the sudden increase in biodiversity by exploring this natural phenomenon. Events of Increased Biodiversity: Evolutionary Radiations in the Fossil Record explores this natural phenomenon of adaptive radiation including its effect on the increase in biodiversity events, their contribution to the changes and limitations in the fossil record, and examines the links between ecology and paleontology's study of radiation.
Chapter 3: The Phenomenon of Evolutionary Radiation 3.1. What is an Evolutionary Radiation?; 3.2. The Different Categories of Evolutionary Radiations, and Their Causes; Chapter 4: Examples of Evolutionary Radiations; 4.1. A Paleontological Bestseller: The Cambrian Explosion; 4.2. Cascaded Radiations: The Case of Ammonites; 4.3. Floral Success: The Emergence and Radiation of Flowering Plants; 4.4. Not-so-round Sea Urchins!; Conclusion; Appendix; Bibliography; Index
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed May 15, 2015)
Elsevier
Keywords: Biodiversity; Animals, Fossil; BUSINESS & ECONOMICS / Real Estate / General; Biomass energy; Paleobiology -- History; Paleontology -- History; Fossil; Adaptive Radiation; Umweltver$1-W[(Bderung.s; 0; Artbildung; 0; Animals, Fossil; Biodiversity; Electronic books; Electronic books